If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 3) = 76 Reorder the terms: 5(3 + x) = 76 (3 * 5 + x * 5) = 76 (15 + 5x) = 76 Solving 15 + 5x = 76 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 5x = 76 + -15 Combine like terms: 15 + -15 = 0 0 + 5x = 76 + -15 5x = 76 + -15 Combine like terms: 76 + -15 = 61 5x = 61 Divide each side by '5'. x = 12.2 Simplifying x = 12.2
| 3r-39=54 | | 6b+7=3b+28 | | 4+5u=0 | | 3s+4=1 | | -2+2s=-8 | | 5c+13=10c+33 | | 7+10x=47 | | 20u^2+21u+4=0 | | 2In(x+3)=In(x+5) | | -10=-4+3G | | 11a+11b+4c+4c-2b-2a= | | 4a(2a+2)=0 | | 3(4x+3)=9x+12 | | 2=k/3-2 | | 9c-16=2 | | 18x-2=24 | | 3j-12=-3 | | 2x+62=5x-17 | | n/2+4=-6 | | -6y-13=8y+15 | | G-8=-27 | | 3x-7=5x*9 | | g/3-7=6 | | 4x-3x-2=21 | | -9m+(-6)=93 | | 2=yx+x | | f(x)=100(0.7) | | r/2+8=9 | | 2=yx+y | | 16-3x+5x=180 | | 7m+2m+8m-6= | | .95=logx |